Associação de megabacteriose, aspergilose e candidíase em periquitos australianos (Melopsittacus undulatus) em cativeiro, Marília, SP: relato de caso - Silva, Tarcísio Macedo [UNESP]; Okamoto, Adriano Sakai [UNESP]; Smaniotto, Bruna Domeneghetti [UNESP]; Pavan, Leonardo Fabrício [UNESP]; Andreatti Filho, Raphael Lucio [UNESP] (Editora Cubo, 2014)
Fungal infections caused by Macrorhabdus ornithogaster, Aspergillus flavus, Candida albicans has been described as responsible for promoting gastrointestinal, respiratory, neurological and dermatological disorders in several avian species. The present paper describes the clinical signs, histopathological exams, treatment and preventions and of a chronic case of three fungal infections concomitant in australian parakeet (Melopsittacus undulatus). The animals came from a commercial breeding facility and sent to Ornitopathology Laboratory of the Veterinary Hospital, Veterinary Medicine and Animal Science Faculty, Paulista State University (FMVZ - UNESP), Botucatu campus - São Paulo, Brazil.

Infecções fúngicas causadas por Macrorhabdus ornithogaster, Aspergillus flavus, Candida albicans tem sido descritas em várias espécies aviárias sendo responsáveis por promover alterações gastrointestinais, respiratórias, neurológicas e dermatológicas entre outras. O presente artigo descreve aspectos clínicos, anatomopatológicos, procedimentos diagnósticos, medidas preventivas e terapêuticas de um caso crônico de três infecções fúngicas concomitantes em periquitos australianos (Melopsittacus undulatus) provenientes de um criatório comercial encaminhado ao laboratório de Ornitopatologia do Hospital Veterinário da Faculdade de Medicina Veterinária e Zootecnia da Universidade Estadual Paulista (FMVZ – UNESP), campus Botucatu – São Paulo, Brasil.
Association megabacteriosis, aspergillosis and candidiasis in australian parakeet (Melopsittacus undulatus) in captivity, Marilia, SP: case report
Keywords: Aspergillus flavus; Macrorhabdus ornithogaster; Candida albicans; Fungus; Pscittacidae; Aspergillus flavus; Macrorhabdus ornithogaster; Candida albicans; Fungo; Psitacídeos